Social networks, Learning, and Flexibility: Sourcing Scientific Knowledge in New Biotechnology Firms - Liebeskind, Julia Porter; Oliver, Amalya Lumerman; Zucker, Lynne; Brewer, Marilynn (Organization Science, 1996)
We examine how two highly successful new biotechnology firms (NBFs) source their most critical input—scientific knowledge. We find that scientists at the two NBFs enter into large numbers of collaborative research efforts with scientists at other organizations, especially universities. Formal market contracts are rarely used to govern these exchanges of scientific knowledge. Our findings suggest that the use of boundary-spanning social networks by the two NBFs increases both their learning and their flexibility in ways that would not be possible within a self-contained hierarchical organization.